LEGAL REGULATION OF STATE SUPPORT MEASURES FOR RUSSIAN BANKS AT THE PRESENT STAGE - Lyudmila G. Pushkina (Russian Studies in Law and Politics)
The article examines the legal regulation of state support measures for banks of the Russian Federation at the present stage. The adopted normative legal acts aimed at adapting credit institutions to long-term structural changes in the banking sector are analyzed. Special attention is paid to the measures taken in 2022 in connection with the changing geopolitical situation and the imposition of sanctions. The work evaluates the effectiveness of these measures and their impact on the activities of credit institutions. In conclusion, the author concludes that it is necessary to introduce a new regulatory document that will regulate the process of creating and publishing doctrinal materials of the Central Bank, including those that the Central Bank develops on its own initiative.